Equity theory predictions of the effects of participation in justice or Police studies on the promotional expectations of members of the Western Australian Police Force - Boaks, William J. (1995)
Before 1988 police in this State were promoted solely on seniority. No university courses for officers existed locally and education played little part in promotion. Promotion is now on the basis of merit and Edith Cowan University conducts courses in Police and Justice Studies. This study investigates possible links between the factors of higher education and merit based promotion. Predictions of student officers' of the benefits of higher education, organisational commitment and various aspects of non-promotion were examined by use of a questionnaire. The results showed that student officers placed a higher value on education for basic police work and managerial ranks. They also considered that they should receive preference for promotion over officers without degrees. There was no differences in current levels of organisational commitment but student officers appeared more likely to experience greater reductions in work effort and desire to remain with the Force if not promoted. They were also found to place greater value on positions using their qualifications as compensation for lack of promotion. Problems and suggested solutions arising from these findings are discussed